Development of Multiple Representation Based Assessment Instruments to Measure Students' Conceptual Understanding of Buffer Solution Material - Rehamita. S, Rehamita. S; Linda, Roza; Futra, Dedi (FKIP - Universitas Riau, 2024)
Buffer solution material was chosen in the process of developing an instrument based on multiple representations, because the buffer solution material contains many representations. Buffer solution material requires explanations in various forms of representation that can visualize the buffer solution material so that students are expected to be able to observe the symptoms that occur and analyze and draw more comprehensive conclusions. This study aims to measure students' conceptual understanding of buffer solution material based on aspects of material, language, construction, and conceptual understanding. The method used is Research and Development with the ADDIE model, involving two schools, SMAN 1 and SMAN 7 Pekanbaru. The validation results by three expert lecturers showed Aiken's (V) values ranging from 0.88-0.97, with instrument reliability stated as good (Cronbach's alpha = 0.815). The level of difficulty of the questions consisted of 4% easy, 84% moderate, and 12% difficult. Measurement of conceptual understanding in 50 students showed a significant difference with a significance value of 0.012 <0.05, so H0 was rejected. The assessment instrument was declared valid and reliable for buffer solution material.